Associations between retirement reasons, chronic pain, athletic identity, and depressive symptoms among former professional footballers. Issue 10 (26th November 2017) - Sanders, George; Stevinson, Clare
Abstract: Background: Retirement from professional sport has been recognised as a major psychological stressor, and there is a need to identify factors that increase the risk of mental health problems after career termination. The current study examined associations between career-ending injury, chronic pain, athletic identity, and depressive symptomology in retired professional footballers. Methods: A cross-sectional study was performed with 307 retired male footballers who had played within a professional United Kingdom league. Participants completed measures of depressive symptoms (Short Depression-Happiness Scale), chronic pain (Pain Intensity Numerical Rating Scale), and athletic identity (Athletic Identity Measurement Scale), and reported their reasons for retirement. Results: A total of 48 participants (16%) met the cut-off score for possible cases of clinically relevant depression. These participants were more recently retired, and had higher athletic identity than those without depressive symptoms. Former players with depressive symptoms were more likely to cite injury as a retirement reason, and report higher levels of ongoing injury-related pain. Multivariate logistic regression revealed that the presence of depressive symptoms was independently associated with retirement through injury (OR = 3.44; 95% CI = 1.39, 8.51), higher pain levels (OR = 1.38; 95% CI = 1.02, 1.86), and increased athl etic identity (OR = 1.28; 95% CI = 1.14, 1.44). Conclusions: Career-ending injury is strongly associated with higher odds of depressive symptomology during retirement, while experiencing chronic pain, and maintaining a high sense of athletic identity, are additional potential contributors.